2000
DOI: 10.1108/01443570010343744
|View full text |Cite
|
Sign up to set email alerts
|

A framework for the selection of best practices

Abstract: Posits that disappointing results from the implementation of best practices are due to a failure to link practices to specific measurable objectives, failure to prioritise best practices, and a lack of analysis of necessary infrastructure practices. Describes the development of a framework for selecting practices which will improve operational performance in the area of manufacturing planning and control. Suggests that selection should be based on strength of relationships between practices and performance obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 11 publications
0
41
1
Order By: Relevance
“…Purcell (1999) questioned whether any bundle of best practices was universally applicable and stressed the importance of understanding the circumstances in which practices applied. Davies and Kochhar (2000) suggested that practices needed to be prioritized based on the effect they were expected or likely to have on desired performance outcomes so as to distinguish the vital few from the useful many. They also suggested that the sequence in which best practices were implemented was also important, with the implementation of some practices being dependent on optimal conditions being in place to ensure success, including supporting practices and appropriate infrastructure.…”
Section: A Critique Of the Best Practice Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Purcell (1999) questioned whether any bundle of best practices was universally applicable and stressed the importance of understanding the circumstances in which practices applied. Davies and Kochhar (2000) suggested that practices needed to be prioritized based on the effect they were expected or likely to have on desired performance outcomes so as to distinguish the vital few from the useful many. They also suggested that the sequence in which best practices were implemented was also important, with the implementation of some practices being dependent on optimal conditions being in place to ensure success, including supporting practices and appropriate infrastructure.…”
Section: A Critique Of the Best Practice Approachmentioning
confidence: 99%
“…The best practice approach to business performance and excellence has been critiqued along several grounds including: Practices need to be context specific and prioritized (Purcell, 1999); relationship between best practices and performance (Davies & Kochhar, 2000); adoption of best practices is insufficient to emulate success of key players (Szulanski, 1996); challenges in selecting and applying best practices (Brannan, Durose, John, & Wolman, 2008); loss of meaning resulting from increased use of best practice terminology (Dani et al, 2006;Patton, 2001); better practices rather than best (Patton, 2001;Smith & Sutton, 1999).…”
Section: A Critique Of the Best Practice Approachmentioning
confidence: 99%
“…Benchmarking is a means of improving business or organizational performance. Davis and Kochhar [27] strongly argue that, to be truly effective, benchmarking needs to be devolved to other contributing levels within a business. Benefits that can be derived from such action are that performance measures and associated targets for strategic objectives can be devolved throughout the organization and focused on the areas that can satisfy them.…”
Section: Developing the Best Practice Methodologymentioning
confidence: 99%
“…BPS is a company wide, firm-developed, ICT system aimed at supporting a process-oriented organizational structure focusing on developing, sharing and applying operating routines, and supply relevant documentation linked to work-practicing routines. BPS is in HAL termed a knowledge management system (KMS) while operating routines are called best practice (Davies & Kochhar, 2000, Voss et al, 1997Voss et al, 1995). We will in this study apply best practice as operating routines (Eisenhardt & Martin, 2000).…”
Section: Research Settingmentioning
confidence: 99%